Travel time to livestock markets,dairy markets, input suppliers, livestock service providers, financial credit providers, and water bodies - Fraval, Simon; Mutua, John Y.; Notenbaert, An Maria Omer; Thornton, Philip K.; Duncan, Alan J. (International Center for Tropical Agriculture, 2020)
The Techfit tool provides a means to identify suitable feed technologies to address four key constraints: dry season feed availability, growing season feed availability, feed quantity and feed quality. The feasibility of introducing each technology is assessed using proxies for seven attributes: land availability, water availability, labour, capital expenditure, access to inputs, requirement for skill/knowledge and market-pull. Travel time to financial service providers, input providers and market outlets were generated based on financial and agricultural points of interest (POI) and a travel friction surface layer. Financial and agricultural points of interest are available for Uganda and Kenya through the FinScope database. The database identifies the locations of credit facilities, abattoirs, sale-yards, milk chilling plants, dairy processors and input suppliers. The points of interests were filtered to only include operational facilities. The travel time to these points were then calculated as the accumulated cost from a given pixel to a POI, where the cost in minutes is defined by the friction layer (accumulated cost calculated using the accCost function in the gDistance package in R). Separate layers were created for financial services, livestock market outlets, dairy market outlets veterinary service providers and agri-input suppliers.